Perlindungan Hukum bagi Investor akibat Initial Public Offering yang Mengandung Misleading Disclosure oleh Liability Underwriter - Muhammad Rafi Farabi; Barbie Puteri; Dylan Budiono Putra (Pemuliaan Keadilan, 2026)
An Initial Public Offering (IPO) is a capital-raising mechanism in the capital market that is fundamentally based on the principle of information disclosure to ensure investor protection. However, in practice, prospectuses may contain false, incomplete, or misleading information (misleading disclosure), potentially causing financial losses to investors. Responsibility for such disclosure extends beyond the issuing company to the underwriter, who is obligated to conduct due diligence and ensure the accuracy and completeness of the information presented in the prospectus. This study aims to analyze the legal liability of underwriters involved in misleading disclosure during IPOs and to examine the legal protection available to affected investors. The research employs a normative juridical method using statutory and library approaches by reviewing Indonesian capital market regulations, including Law Number 8 of 1995 on the Capital Market, Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector, and regulations issued by the Financial Services Authority (OJK). The findings indicate that underwriters may be held administratively, civilly, and criminally liable if proven responsible for misleading disclosure. Investor protection is provided through preventive mechanisms, such as disclosure principles, OJK supervision, and due diligence, as well as repressive mechanisms, including compensation claims, dispute resolution, and legal sanctions. Nevertheless, the effectiveness of these protections depends on consistent supervision and law enforcement.